Chloe : a novel of secrets and lies - Briscoe, Connie (Amistad, an imprint of HarperCollinsPublishers, 2025)
"Angel is a private chef for the Harrison's, one of the most powerful Black families on Martha's Vineyard. Impossibly supercilious Jillian Harrison often spends the entire summer on the island, while her husband Irvin and their twenty-nine-year-old daughter Norma commute from Washington, DC, on weekends. They always join Jillian for the month of August, when the family throws a lavish garden party on the expansive lawn that is attended by nearly one hundred guests. This year's guests include Everett Bruce, an influential Black billionaire, still in mourning for his first wife, Chloe, who committed suicide. To the imperious Jillian's surprise, Bruce ignores her and instead becomes enchanted with Angel. Eager to get away from the controlling Mrs. Harrison, Angel accepts Everett's invitation to become the private chef at Riverwild, his massive mansion along the Potomac River. Her meals and company provide comfort to Everett, and soon he and Angel begin a whirlwind romance that culminates in marriage. Though Angel is confident and strong, over time, she begins to feel the enigmatic Chloe's ghost. The house's staff, the head housekeeper Ida--a menacingly rigid thorn in Angel's side--and even Everett, cannot seem to let the dead woman go, nor explain why the wealthy, stunning woman would kill herself. The more questions Angel asks, the more melancholic Everett becomes, revealing a far less charming side of himself. Just how well does Angel know Everett? Did she marry in haste? The answers lie somewhere in Riverwild..." --